Development and Demonstration of a Novel Reversible SOFC System for Utility and Micro Grid Energy Storage1. Issue 4 (17th January 2017) - Mermelstein, Joshua; Posdziech, Oliver
Abstract: Energy storage is a critical component to supply local energy generation for both grid and off‐grid connected facilities and communities, enabling localized grid independent energy secure power in cases of emergencies or unreliable traditional grid use. The high cost and energy security of importing fuel to islanded grids has led to a growing need to generate power onsite with alternative and renewable energy technologies while reducing facility costs of importing electrical power. However, utility grid operators are being faced with the challenges of intermittent and variability in energy production from renewables. Therefore, energy storage is crucial to balance micro and utility grids, improve efficiency, reduce fuel consumption, and provide critical power in the event of power outages. There has been particular interest in reversible solid oxide fuel cells (RSOFCs) in the energy sector for electricity, energy storage, grid stabilization and improvement to power plant system efficiency due to favorable thermodynamic efficiencies of high temperature steam electrolysis. Boeing has been active in the development of a fully integrated, grid tied RSOFC system for micro grid and commercial utility energy storage using Sunfire fuel cell technology. In this system, excess grid energy or curtailed power generated by renewables is sent to the system operating in electrolysis mode to produce H2 . The H2 is stored and then used in the system's fuel cell mode to provide supplemental power to the grid during peak hours or as needed. As part of this program, Boeing has developed a H2 storage and compression system, power distribution system, and master controller to interface with RSOFC subsystems. Sunfire developed a reversible solid oxide cell module with a power output of 50 kW in SOFC mode and 120 kW input in electrolysis mode producing 3.5 kg H2 hr −1 . The system was demonstrated while connected to the local utility grid and operated in a microgrid test environment. This paper will discuss the development, integration, and demonstration of the RSOFC system.